Japan : doing business in a unique culture - Bucknall, Kevin B. (Boson Books, 2005)
This book is essential reading for all those managers, investors, and traders as well as government officials who do business in or might in the future have dealings with Japan. More than most people living in a rich, developed country, the Japanese still place great store on traditional values and cling to a culture that is both varied and unique. Business etiquette and general good manners are not only dissimilar, but they are strictly prescribed and adhered to by those with whom you will negotiate and socialize. Getting things right can only help you, but it is incredibly easy to get things.